The role of glycemic traits in the mediation of the causal effect of hypothyroidism on coronary heart disease - Jin, Zhiwei; Li, Guorong; Xue, Zekuan; Li, Yijie; Yang, Wangfang; Yu, Yunfei; Hou, Jixue (Frontiers in Endocrinology, 2024)
Background Hypothyroidism and coronary heart disease are both common diseases in life and both are increasing in prevalence. Many studies have found a strong association between the two. However, they have not been able to prove a causal relationship. Furthermore, numerous studies have demonstrated that glycemic traits play a role in both. Consequently, the objective of this study was to ascertain the causal estimation of the association between hypothyroidism and coronary heart disease and to quantify the potential mediating role of glycemic traits in this relationship. Methods We used two-sample Mendelian randomisation (UVMR) to explore causality between hypothyroidism and coronary heart disease. Additionally, multivariate Mendelian randomisation (MVMR) was applied to quantify the potential mediation of glycemic traits in this relationship. A variety of Mendelian randomization methods were employed in this study, including the inverse variance weighting (IVW) method, weighted median method, and MR-Egger test. Heterogeneity and horizontal pleiotropy were evaluated through MR-Egger intercept test, Cochran’s Q test, and leave-one-out analysis to ensure the robustness of the study results. Results The results of the MR analyses indicated that hypothyroidism was associated with an increased risk of coronary heart disease (IVW: OR=2.75, 95% CI: 1.53-4.94). In mediation analyses, the proportion of HbA1c-mediated effects of hypothyroidism on coronary heart disease was 7.3% (2.2%-12.5%). Conclusion The results of our study indicate a causal relationship between hypothyroidism and coronary heart disease. Furthermore, HbA1c partially mediated the causal effect of hypothyroidism on coronary heart disease. Consequently, intervention in this factor may reduce the risk of coronary heart disease associated with hypothyroidism.